Adaptação de cultivares diploides e tetraploides de azevém anual às condições climáticas do sudoeste do Paraná - Aiolfi, Ricardo Beffart (2016)
Annual ryegrass is one of the species that best meets the needs of ranchers of southern Brazil during the winter period of the year. The breeding of ryegrass for many years has been developing superior materials, diploid and tetraploid, which, despite its higher prices for seed are being used by producers because of their better performance and quality. The objective of this research was to evaluate the behavior of different cultivars of Italian ryegrass - diploid and tetraploid, grazing, climate conditions of southwestern Paraná. The experiment was conducted in the city of Pato Branco / PR. The experimental design was a randomized block design with four replications. The observed cultivars were: LE 284, Camaro, Bakarat, Estações, Ponteio and Nibbio (diploid) and Winter Star, KLM 138, Escorpio, Titan, Barjumbo and Potro (tetraploid). The grazing was mob-grazing type time respecting input of 25 cm and 10 cm high output. It was observed that the cultivars that had high period of pasture use were those that produced larger amounts of forage. For all cultivars the highest forage accumulations occur between the months of August, September and October. Tetraploid have lower population density of tillers, but this does not affect the IAF among cultivars nor the interception of solar radiation before and after the completion of a grazing. NDF and ADF contents linearly increase with advancing in ryegrass cultivars development cycle. On average, tetraploid cultivars produce larger amounts of forage in relation to diploid cultivars.